BIMBINGAN PERKAWINAN UNTUK MENCEGAH STUNTING: PERSPEKTIF MASLAHAH MURSALAH - Aminuddin, Aminuddin; Pagar, Pagar (Pusat Studi Gender dan Anak, 2024)
This study focuses on marriage guidance to reduce stunting. One of the biggest nutrition problems in the world is stunting, and Indonesia still faces this problem today. Stunting is when babies do not grow properly due to infections and nutritional deficiencies during their first thousand days of life. The purpose of marriage guidance is to reduce the prevalence of stunting, increase the education needed to prepare for family life, and improve how to care for children. Primary and secondary data were used as sources in a qualitative research method. The findings of this study are that marriage guidance to Muslim brides and grooms can help them adopt a healthy lifestyle and improve their nutrition. Thus, this study has the potential to reduce the prevalence of stunted generations. Marriage guidance aims to let the bride-to-be know whether she will have healthy offspring after her marriage, as stunting can occur as a result of an unhealthy couple. Thus, marriage in Islam aims to build a family that is peaceful, peaceful.